The Effect of Online Learning on Academic Writing Course During Covid-19 Pandemic - Syamsiarna Nappu; Ratna Dewi; Hasnawati Hasnawati; Radiah Hamid (Universitas Hamzanwadi, 2022)
Since the outbreak of Covid 19 in Indonesia, all universities, including Universitas Muhammadiyah Makassar, had made a decision for lecturers and students to learn from home (LFH) since March 16, 2020. This decision certainly has an impact on the change of the learning process which is used to face-to-face in the classroom then drastically changed and become online learning. This study aims at investigating the effectiveness of online learning on the Academic Writing course in the English Education Study Program. Pre-experimental design is the method where the sample is purposively chosen. The data is collected by giving pre-test and post-test and questionnaire. The study reveals that students get better writing skills after learning online. It can be seen that the pretest is 50.6 becomes 75.8 in the posttest. Meanwhile, after calculating the t-test it is also found that the effectiveness of online learning on Academic Writing Course through Google Meet is 55%. It is then concluded that online learning using Google Meet on Academic Writing Course has a positive effect on students' writing skills.